TINJAUAN YURIDIS TERHADAP TINDAKAN MENGHALANGI PEMBERIAN ASI EKSKLUSIF - Ni Komang Ratih Kumala Dewi (Jurnal Analisis Hukum, 2018)
Mother is a woman who has given birth to her child with difficulty, terrible pain, to risk her life, from the beginning of her pregnancy for nine months, the mother who cares for the baby to be born safely. Certainly it is appropriate that a mother is also able to give exclusive breastfeeding to the baby who was born. Breast milk as the best food for baby no doubt. But lately it is unfortunate many of mothers meyusui forget the benefits of breastfeeding. Therefore, it is very important that a Government Regulation governing the provision of Exclusive Asi and sanctions if one tries to prevent Exclusive Breastfeeding.Key words : Mother, ASI Eksklusif, Government Regulation